Estudos avaliativos do desempenho do aplicativo APR através de casos reais de consumidores da região metropolitana de Cuiabá - Quadrado Júnior, José Nelson (2012)
In the last years the refunding requests for damages in electric and electronic equipments have been increasing substantially and this subject has deserved the attention of electric power utilities, regulation agencies, consumers and other government organizations. Such concerns have emerged the theme referred in this dissertation which aims at establishing the first steps towards the validation of a computational program - APR developed at the Federal University of Uberlandia. This software is to be used to provide reports about specific refunding requests throughout technical and scientific electrical fundaments. The strategy here focused is based on the comparison of real cases computational results from the APR to the traditional procedures followed by of electric power utilities. To achieve such goals the studies are carried out in accordance with the following sequence: consumer claimer\'s identification, modeling the respective feeder circuit, disturbance simulation, selection of the claimed equipment and, at the end, the determination of the correlation among the distribution system disturbances causing dielectric and thermal effects applied at the claimed equipment and the corresponding tolerances allowed in terms of the device supportability limits. Following the above steps it becomes clear that the APR applicative is then submitted to a first level of a validation strategy toward the achievement of a reliable, rapid and consistent computational tool to help decisions about equipment damage requests.